The Effectiveness of the EGP Method (Emotional, Fast Action, Revision) in the Short Story Writing Ability of Madrasah Aliyah Students - Sulkifli, Sulkifli; Islamiah, Ainul; Akbar, Fadly; Salam, Abd. Latif (State Islamic Institute of Palopo, 2024)
The Effectiveness of the EGP Method (Emotional, Fast Action, Revision) in the Short Story Writing Ability of Class XI Students of MA DDI Gusung Makassar. This study aims to determine: (1) the ability to write short stories using direct learning (2) to determine the ability to write short stories using the EGP method (Emotional, Fast Action, Revision) (3) the effectiveness of the EGP method (Emotional, Fast Action, Revision) in the short story writing ability of class XI students of MA DDI Gusung Makassar. This study was conducted at MA DDI Gusung Makassar. The research approach used in this study is a quantitative approach. The type of research used in this study is experimental research involving one group that is given treatment. Before being given treatment, students are given a pretest and after being given treatment, students are given a posttest to measure the ability to write short stories in the subject group. The results of the pretest and posttest in this study will show the results of the treatment that has been given. Based on the research results, it was concluded that (1) the pretest and posttest scores were above the KKM score but there was a significant increase of 16.94. (2) the average N Gain score for learning outcomes in short story writing skills after being given learning using the EGP (Emotional, Fast Action, Revision) learning model was 0.57 or 57% which means it is in the fairly effective category. (3) hypothesis testing with a paired sample test showed that there was a significant difference in learning outcomes before and after the EGP (Emotional, Fast Action, Revision) learning method was applied in students' ability to write short stories in class XI MA DDI Gusung Makassar which also means that the application of the EGP (Emotional, Fast Action, Revision) learning method was declared effective in improving students' ability to write short stories in class XI MA DDI Gusung Makassar